Pragmatic Language of Students with Learning Disabilities: Cross-Cultural Research - Suhail Mahmoud Al-Zoubi (Qubahan Academic Journal)
This cross-cultural descriptive research aimed to identify the level of pragmatic language (PL) among students with learning disabilities (LDs) as perceived by the teachers of the resource room program (RRP) in Jordan and Oman. The research sample consisted of 453 Jordanian and Omani students with LDs enrolled in the RRP. To achieve the objectives of this research, teachers of RRP responded to the Children's Communication Checklist (CCC) that was translated into Arabic [1]. The CCC consisted of 38 items distributed into five subdimensions: inappropriate initiation; coherence; stereotyped language; use of context; and rapport. The results showed that the mean of PL level on all subdimensions of CCC was low among students with LDs. The results of the MANOVA test showed that there were statistically significant differences in PL in favor of female students in Jordan and Oman. The results of the t-test showed no statistically significant differences in PL due to country (Jordan and Oman). The research recommended that students with LDs be enrolled in counseling programs based on PL skills and that families have a vital role in teaching these skills to their children.